BEDA PENGARUH ANTARA PEMBERIAN CONTRACT RELAX DENGAN HOLD RELAX TERHADAP PENINGKATAN FLEKSIBILITAS OTOT HAMSTRING PADA ATLET SMAN 18 MAKASSAR - La Ode Muhammad Syarwan; Darwis Durahim (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background: Flexibility is the ability of a tissue or muscle to experience maximum lengthening so that the body can move with the full range of motion of the joints, without the onset of pain. Decreased hamstring flexibility can be caused by several factors, such as shortening of the hamstring muscles, acute or chronic injury to the hamstring muscles, decreased hip joint, excessive activity, and improper training patterns.Methods: This study was a quasi-experimental study using a two-group pre-test and post-test design. The aim was to determine the different effects of the Contract Relax intervention compared to the Hold Relax on increasing the flexibility of the Hamstring muscles. This research was conducted at SMA N 18 Makassar, with the sample being students who fit the inclusion criteria. The number of samples was 20 people who were randomly divided into 2 groups, namely the treatment group I who were given Contract Relax as many as 10 people and the treatment group II who were given Hold Relax as many as 10 people.Results: Based on the analysis of the paired sample t-test in the treatment group I obtained a p value <0.05 with pre and post test results of 0.00 for the Sit and Reach value which means that Contract Relax can result in a significant increase in Hamstring muscle flexibility. While the treatment group II also obtained a p value <0.05 with pre and post test results of 0.00 for the Sit and Reach value which means that holding Relax can result in a significant increase in Hamstring muscle flexibility. Then based on the Independent sample t-test, a p value <0.05 was obtained for the Sit and Reach value, which means that Hold Relax is significantly more effective than Contract Relax for increasing hamstring muscle flexibility.Conclusion : Hold Relax is better than Contract Relax in increasing the flexibility of the Hamstring musclesKeywords: Contract Relax, Hold Relax, Hamstring Flexibility